Effect of fertiliser application and cutting regime on temporal differentiation of mesic semi-natural grassland vegetation - Čop, Jure; Eler, Klemen (Italian Journal of Agronomy, 2019)
To address biodiversity and agronomic value of grasslands, we attempted to determine the effect of management regimes on temporal plant species diversity of Arrhenatherion grassland vegetation over a 7-year period. In a split-plot experiment, three cutting regimes (traditional 2-cut system, modified and regular 4-cut systems) and five fertilisation regimes [i) zero; ii) phosphoruspotassium (PK); iii) cattle slurry; iv) nitrogen-PK (NPK) plus cattle slurry; v) NPK] were assigned to the main plots and the subplots, respectively. Significant temporal changes in plant species composition, abundance of functional groups, plant richness and Shannon index were found for most investigated regimes. The effects of fertilisation regimes on all investigated parameters were much stronger than cutting regimes. Generally, two distinct pathways of sward compositional development were found, depending on whether the mineral N was added or not. Differentiation in the plant species composition and abundance of functional groups started in the second year and continued with the progress of the experiment. A quite distinct pattern of change in the plant species composition was found for PK where initially higher abundance of legumes triggered the sward development similar to the slurryfertilisation regime. The fertilisation with high N rates caused temporal decrease in species richness and Shannon index. Other fertilisation treatments did not affect these two diversity parameters in a seven-year period. The cutting regimes did not temporally differentiate the sward regarding plant species composition and abundance of functional groups. They affected only plant species composition in the seventh year and indicated some effect on the temporal change of Shannon index.